School Learners' Relationships as an Object of Educational Research under Globalization - Aramavičiūtė, Vanda; Martišauskienė, Elvyda (Acta Paedagogica Vilnensia, 2007)
The present article is an attempt to discuss the role of culture within the context of globalization and to describe the dialectical inter-relationship between culture and globalization. The article is also aimed at revealing the attitudes of both the researchers of globalization and the experts of culture towards the impact of globalized culture on people's relationships. Within this context, new forms of mediation based communication can be brought forward as well as their possible outcomes to effect the process of individual's spiritual self-becoming. Due consideration of some issues of emancipation and manifestations of individualism as reflected in people's relationships also finds place in the article. On the basis of the data obtained from empirical research, the characteristics of school students' human relationships with their parents, teachers, peers and themselves in forms 7 to 9 and 10 to 11 are discussed. Some evidence is presented of how those relationships were conditioned by age and gender and how school students tended to value those relationships. Most clearly manifested regression could be observed in the school students' valuations of their relationships with themselves and their teachers, and the smallest degree of regression was found in the student's relationships with the mother. The relationships with peers also tended to be characterized as of decreasing human quality.
Keywords: globalization; culture; relationships; values; humaneness